Wildfire Dynamics in the Guanacaste Conservation Area During 1997-2017: Ecological Perspectives for Overall Fire Management - Jones Román, Gabriela (2018)
his article analyzes wildfire dynamics regarding fire ecology in the Guanacaste Conservation Area, which is the largest area of tropical dry forest in Costa Rica. Over the last two decades there have been fires in the conservation area, with the highest recurrence in the El Hacha, Murciélago, and Santa Elena sectors. Contrary to the expectations, the years of greatest fire damage do not coincide with El Niño events. Evidence is presented of the vulnerability of certain vertebrate groups and the adaptive responses of certain plant species to fires. The impact of fires is discussed within an integrated fire management framework considering adaptation of certain species, plant succession, and habitat differentiation. It is concluded that fire suppression in habitats with fire dependence and recurrence should be analyzed in more detail to ensure the conservation and resilience of several biodiversity components in this ecosystem.